Legal Protection for Victims of Unilateral Cancellation of Marriage Following Engagement - Roy Ronny Lembong; Harly Stanly Muaja; Hironimus Tororeh (Jurnal Ilmu Hukum Kyadiren, 2026)
The unilateral cancellation of marriage following engagement may cause significant legal harm because Indonesian law does not explicitly regulate pre-marital legal relationships. This study examines the legal consequences of such cancellations and evaluates the effectiveness of existing legal protection under Law No. 1 of 1974 on Marriage, as amended by Law No. 16 of 2019, Articles 58 and 1365 of the Indonesian Civil Code, relevant legal doctrines, and judicial precedents. Using a normative legal research method with statutory, conceptual, and case approaches, the study analyzes primary, secondary, and tertiary legal materials. The findings indicate that unilateral cancellation following engagement constitutes a tort by causing economic, non-economic, social, psychological, and cultural harm. The current legal framework remains predominantly remedial, creating legal uncertainty. Therefore, regulatory reform is needed to establish integrated preventive and remedial legal protection for affected parties.